Diagnostic value of olfactory function testing for Alzheimer’s disease and mild cognitive impairment: a systematic review and meta-analysis - Liu, Yuxuan; Cao, Yunpeng; Wei, Hongquan (Frontiers in Aging Neuroscience, 2025)
BackgroundAlzheimer’s disease (AD) is clinically classified into prodromal (asymptomatic), mild cognitive impairment (MCI) due to AD, and dementia due to AD. This study investigates the diagnostic value of olfactory function testing for AD and MCI.MethodsSystematic searches of PubMed, Web of Science, Cochrane, and EMBASE databases were conducted up to February 1, 2024. Methodological quality was assessed using the revised Quality Assessment of Diagnostic Accuracy Studies. Effect sizes were combined using a random-effects model (DerSimonian-Laird method), and statistical analyses were conducted using STATA 15.1 and Meta-Disc 1.4 software.ResultsTwenty-five studies with 13,611 participants were included. For diagnosing AD, combined sensitivity (SE) was 0.79 (95% CI: 0.71–0.85), specificity (SP) was 0.78 (95% CI: 0.69–0.84), and AUC was 0.85 (95% CI: 0.82–0.88). For MCI, SE was 0.67 (95% CI: 0.54–0.78), SP was 0.79 (95% CI: 0.71–0.86), and AUC was 0.81 (95% CI: 0.77–0.84). Combined SE and SP for diagnosing AD and MCI were 0.58 (95% CI: 0.46–0.68) and 0.88 (95% CI: 0.78–0.93), with an AUC of 0.78 (95% CI: 0.74–0.82). SE and SP for AD or MCI were 0.83 (95% CI: 0.36–0.98) and 0.94 (95% CI: 0.82–0.98), with an AUC of 0.96 (95% CI: 0.94–0.98).ConclusionThis systematic review and meta-analysis reveal that olfactory function testing, as a simple, non-invasive, and cost-effective assessment method, demonstrates high diagnostic efficacy in the early identification of AD and MCI, showing promising clinical application.Systematic review registrationCRD42024520871.